Bibliometric Analysis of Waqf Education on Google Scholar from 2019 to 2022 using VOSviewer - Rusli, Radif Khotamir; Hafidhuddin , Didin; Bahruddin , Ending; Tamam, Abi Mansur; Ibnu , Adi Rahmanur (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
Bibliometric analysis using data on the number and authors of scientific publications as well as articles and citations in them aims to measure the outcomes of researchers, institutions, and countries, in order to identify national and international networks and map the development of new (multidisciplinary) fields of science and technology, this is also known as known as Scientometrics. While, VOSviewer is software for analyzing bibliometrics in order to find research novelties that have not yet appeared in the realm of science and knowledge. This study aims to analyze waqf education on Google Scholar from 2019 to 2022. This study aims to analyze the bibliometrics of waqf education on the Google Scholar data research. The research method used is using the publish and perish application to collect reference data for the last four years from 2019 to 2022. Then use the VOSviewer application to analyze the bibliometrics by referring to the results generated from the publish and perish application in the form of *.ris and *.xls files. The research findings show that there were 494 publications during the last four years for the 2019-2022 period in the field of waqf education with a total of 734 citations. As for the number of interconnection relationships between terminology in the existing research, it was found that the strongest number of relationships was term waqf of 356, cash waqf of 114, asset of 96, waqf of fund 75, and manager of 73. While the number of frequencies that frequently appeared was term waqf as much as 252 times, Cash waqf 71 times, asset 55 times, land waqf 41 times, and manager 36 times.